Inhibitory effects of Curcumae Radix carbonisata-based carbon dots against liver fibrosis induced by carbon tetrachloride in mice - Yusheng Zhao; Hui Kong; Yuru Li; Yafang Zhao; Yue Zhang; Yan Zhao; Huihua Qu (Artificial Cells, Nanomedicine, and Biotechnology, 2024)
As a processed product of traditional Chinese medicine Curcumae Radix, Curcumae Radix Carbonisata (CRC) has been widely used in the treatment of liver diseases in ancient medical books. In this study, novel carbon dots (CDs) extending from 1.0 to 4.5 nm were separated from fluid extricates of CRC. Meanwhile, a liver fibrosis model induced by carbon tetrachloride (CCl4) was utilized to determine the inhibitory effects of CRC-CDs against liver fibrosis. The results exhibited the CRC-CDs with a quantum yield of 1.34% have a significant inhibitory effect on CCl4-induced liver fibrosis, as demonstrated by improving hepatocyte degeneration and necrosis, inflammatory cell infiltration and fibrotic tissue hyperplasia, downregulating the levels of alanine transaminase (ALT), aspartate aminotransferase (AST), total bilirubin (TBIL), direct bilirubin (DBIL), total bile acid (TBA), triglyceride (TG), tumour necrosis factor-α (TNF-α), interleukin (IL)-6 and IL-1β in the serum, upregulating the contents of superoxide dismutase (SOD), reduced glutathione (GSH), and downregulating the concentration of malondialdehyde (MDA), which lays an important foundation for the development of CRC-CDs as a novel drug for the treatment of liver fibrosis, and provide a certain experimental basis for the clinical application of CRC-CDs in the future.